Knowledge management assessment model for information technology SMEs (2015)
This paper discusses the statistical validation of a knowledge management (KM) assessment model for software-developing SMEs (small and medium-sized enterprises) located in the so called Colombian coffee triangle. A confirmatory correlational research, validated with 110 companies, was carried out taking into account a variety of aspects, namely infrastructure, intensive use of knowledge management and communities of practice (CoP). The model was tested under a confirmatory factor analysis meeting convergence, divergence and joint reliability criteria. A single model for assessing KM was obtained which is based on a holistic approach and a process-driven management. This model assesses 22 variables, 7 categories and 3 dimensions on SMEs pertaining to the information and communications technology industry (ICT). This allows the validation of a theoretical model that suits software companies’ needs, which can be applied to similar sectors in other cities around Colombia and the world.